Strategies for Implementing Telemedicine to Improve the Quality of Healthcare Services: A Literature Review - Yohanes Baptistuta Paser; Mukhammad Hilal; Dimaz Rafly Inzaghi (Publikasi Indonesia, 2026)
Telemedicine, the use of communication technology to provide remote health services, has emerged as a transformative innovation in modern healthcare. This study aims to analyze the impact of telemedicine on healthcare service quality and identify strategies for its effective implementation. A literature review method was employed, sourcing articles from Google Scholar, PubMed, and ScienceDirect databases using keywords including